2001
DOI: 10.1016/s0005-2736(01)00287-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transitions of DMPG bilayers in aqueous solution: SAXS structural studies

Abstract: Dimyristoylphosphatidylglycerol (DMPG) has been extensively studied as a model for biological membranes, since phosphatidylglycerol is the most abundant anionic phospholipid in prokaryotic cells. At low ionic strengths, this lipid presents a peculiar thermal behavior, with two sharp changes in the light scattering profile, at temperatures named here T(on)(m) and T(off)(m). Structural changes involved in the DMPG thermal transitions are here investigated by small angle X-ray scattering (SAXS), and compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
1
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(156 citation statements)
references
References 31 publications
16
129
1
10
Order By: Relevance
“…SAXS patterns in the gel and fluid phases show an isotropic ring suggesting that DMPG forms spherical vesicles as expected [3,7,17]. Broad peak is a characteristic of single bilayer membranes [3,18]. In the intermediate phase at T = 22 and 24°C, on the other hand, anisotropic rheo-SAXS patterns are obviously observed.…”
Section: Rheo-saxssupporting
confidence: 52%
“…SAXS patterns in the gel and fluid phases show an isotropic ring suggesting that DMPG forms spherical vesicles as expected [3,7,17]. Broad peak is a characteristic of single bilayer membranes [3,18]. In the intermediate phase at T = 22 and 24°C, on the other hand, anisotropic rheo-SAXS patterns are obviously observed.…”
Section: Rheo-saxssupporting
confidence: 52%
“…The calculated SAXS curves are similar because the structure of the bilayered membrane is maintained at different temperatures. Nevertheless, the widening of the curves and the consequent shift to higher q values for q ϭ Ͼ2 nm Ϫ1 indicates a thinning of the membrane upon heating (19,20). This analysis showed that when Bacillus membranes are cooled from 37 to 25°C, the hydrophobic thickness increases by 1 Å.…”
Section: Resultsmentioning
confidence: 88%
“…The data were fitted to the commonly used three-layer model, in which the three layers represent (i) the end methyl group of the acyl chains (low electron density), (ii) the central core of the acyl chains (medium electron density), and (iii) the head groups (high electron density). This method allows estimation of lengths perpendicular to the membrane, electron density, and roughness for each slab (19,20). The roughness or smearing at each slab interface, thickness, and electron density were fitted with starting values for diacylphosphyatidylglycerol (19), which is the major lipid of the ensemble.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimyristoylphosphatidylglycerol (DMPG) bilayers have been extensively studied as a model for the negatively charged biomembrane (Eklund et al, 1987;Lotta et al, 1988;Kodama et al, 1993;Zhang et al, 1997;Garidel et al, 2000;Toca-Herrera et al, 2000;Riske et al, 2001;Lamy-Freund and Riske, 2003;Lewis et al, 2005). Recently, it has been reported that DMPG bilayers show a unique low-temperature phase behavior depending on environmental conditions.…”
Section: Introductionmentioning
confidence: 99%